Prinsip Kerja Sama Tuturan Deklaratif Narasumber dalam Kanal Youtube Najwa Shihab Episode “Terima Kasih Pak JK” - Mila Widayanti; Herwandi Herwandi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This study aims to determine the purpose of using declarative utterances and to find out the sources of declarative utterances that meet the principle of cooperation in the use of declarative utterances on Najwa Shihab's youtube channel episode "Thank You Pak JK". This research uses a qualitative approach and the type of this research is library research. The results of this study show 240 declarative utterances from the sources consisting of conveying factual information 107 utterances, stating decisions and judgments of 45 utterances, stating agreements, warnings and advices 13 utterances, expressing congratulation or misfortune 0 utterances, and providing explanations and explanations totaling 75 utterances. In speaking, the speakers convey factual information more to the presenters. In the declarative utterances of resource persons who have met the cooperative principle, there are 163 utterances consisting of 37 utterances of quantity maxim, 11 utterances of quality maxim, 105 utterances of relevance maxim, and 10 utterances of implementation maxim.